Reframing Early Psychiatric Crises: a Capabilities-Informed Approach - Hopper, Kim (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2012)
Spurred by a working conference convened in the fall of 2009 by the Center to Study Recovery in Social Contexts and INTAR (the International Network Towards Alternatives and Recovery), this paper first develops a serviceable version of Sen’s capabilities approach for use in public mental health and then explores how its conceptual toolkit might aid us in rethinking about we approach “first breaks” and early crises. This will be exploratory labor.2 Provisional efforts have been made to use the capabilities approach to rethink recovery and social integration as outcomes, to support self-determination, and to make a case for peer participation in research. This paper shifts the focus from the remedial work of treatment and social re-entry to the preventive work of crisis management and biographical continuity. After sorting through Sen’s approach for grounding principles and heuristic guides – which is here compiled into a sort of primer or toolkit, distilled into 8 key ideas and an anthropological coda on adolescent trial/error – I go on to identify three alternative ways that a capabilities approach might usefully reframe disability and impairment. That done, I make the case for applying the third (or radical) version to the social reception of early crises and try to envision what that might look like in practice.